Prevalence of Urinary Incontinence and Health Seeking Behaviours among Middle Age Women - Shrestha, Kalpana; Niraula, Hira; Silwal, Ajita (Journal of Karnali Academy of Health Sciences, 2022)
Introduction: Urinary incontinence is one of the most common problems of middle-age. It is one of the inconvenient experiences that have adverse physical, psychological and social effects. The shame, taboos and associated knowledge deficit have interfered with its health seeking approaches that further lower the quality of life. This study was designed to assess the prevalence and health seeking behaviour on urinary incontinence among middle aged women. Methods: The community-based descriptive cross sectional study was conducted to find out the prevalence and health seeking behaviours on urinary incontinence among middle aged women. A total number of 175 women of age group 40-60 years were purposively selected from the Kathmandu metropolitan city ward number 31 from among the voters. Face to face interview was conducted using structured interview schedule. Data were analysed using descriptive (frequency, percentage, mean, standard deviation range) statistics. Results: The study showed that 56% of the women had urinary incontinence. Among them 59.18% had stress urinary incontinence, and 40.82% women had both stress and urge urinary incontinence. Among them, 74.5 % women did not seek medical consultation. Some of the common reasons for not seeking medical advices were perceiving urinary incontinence as a natural process (79.22%), lack of knowledge(55.84%) and embarrassment (33.77%). The study findings also showed that urinary incontinence was statistically significant with the age of women, parity, place of delivery and mode of delivery. Conclusions: Urinary incontinence is prevalent in more than half of the women and stress urinary incontinence was common among them. Most of the women had not sought any medical advice. embarrassment, lack of knowledge and perceiving condition as natural were some of the reasons for not approaching for medical consultation.